Preparation and Characterization of a Novel Morphosis of Dextran and Its Derivatization with Polyethyleneimine - Jiang, Zhiming; Sun, Kaifeng; Wu, Hao; Dong, Weiliang; Ma, Jiangfeng; Jiang, Min (Molecules (Basel, Switzerland), 2023)
Dextran, a variant of α-glucan with a significant proportion of α-(1,6) bonds, exhibits remarkable solubility in water. Nonetheless, the precipitation of dextran has been observed in injection vials during storage. The present study aimed to establish a technique for generating insoluble dextran and analyze its structural properties. Additionally, the potential for positively ionizing IS-dextran with polyethyleneimine was explored, with the ultimate objective of utilizing IS-dextran-PEI as a promising support for enzyme immobilization. As a result, IS-dextran was obtained by the process of slow evaporation with an average molecular weight of 6555 Da and a yield exceeding 60%. The calculated crystallinity of IS-dextran, which reaches 93.62%, is indicative of its irregular and dense structure, thereby accounting for its water insolubility. Furthermore, positive charge modification of IS-dextran, coupled with the incorporation of epichlorohydrin, resulted in all zeta potentials of IS-dextran-PEIs exceeding 30 mV, making it a promising supporting factor for enzyme immobilization.